Forgotten voices of Mao's great famine, 1958-1962 : an oral history - Zhou, Xun, 1968- (New Haven : Yale University Press, 2013)
" In 1958, China's revered leader Mao Zedong instituted a program designed to transform his giant nation into a Communist utopia. Called the Great Leap Forward, Mao's grand scheme-like so many other utopian dreams of the 20th century-proved a monumental disaster, resulting in the mass destruction of China's agriculture, industry, and trade while leaving large portions of the countryside forever scarred by man-made environmental disasters. The resulting three-year famine claimed the lives of more than 45 million people in China. In this remarkable oral history of modern China's greatest tragedy, survivors of the cataclysm share their memories of the devastation and loss. The range of voices is wide: city dwellers and peasants, scholars and factory workers, parents who lost children and children who were orphaned in the catastrophe all speak out. Powerful and deeply moving, this unique remembrance of an unnecessary and unhindered catastrophe illuminates a dark recent history that remains officially unacknowledged to this day by the Chinese government and opens a window on a society still feeling the impact of the terrible Great Famine"--
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Famines -- China -- History -- 20th century; Food supply -- China -- History -- 20th century; China -- Population -- History -- 20th century; Electronic books